Development of a Learning Module for Writing Short Stories in the Religious Genre for Elementary School Students - Nurfatwatul Anan; Edhy Rustan (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this research is to find out the needs, develop, and find out the validity of the learning module for writing short stories in the religious genre that has been created. This product development research was carried out concerning the 4D development model, which consisted of four stages: defining, designing, developing, and and disseminating. The research was conducted on students in class IV of SDN 50 Bulu Datu. The instruments used in the study were teacher interviews, teacher questionnaires, student questionnaires, and comprehension tests for students. The data obtained from the agencies were analyzed qualitatively. The results obtained from the needs analysis showed that students liked colourful, pictorial teaching materials. The type of question you are interested in is in the form of multiple choice. Students also want to work on assignments in groups. The development is done by integrating the linguistics of short story material with Islamic religious knowledge, especially the story of the Prophet Muhammad. Product validation by three experts, namely language and material experts, religious content experts, and elementary school instructional design experts, obtained very valid results the module was feasible to use